Intermuscular coherence of plantar and dorsiflexor muscles in older adults with Parkinson’s disease and age-matched controls during bipedal and unipedal stance - Smart, Rowan R.; Toumi, Anis; Harris, Owen D.; Cremoux, Sylvain; Dalton, Brian H.; Wile, Daryl J.; Jakobi, Jennifer M. (Frontiers in Aging Neuroscience, 2023)
Postural instability increases with age and is exacerbated in neurological disorders such as Parkinson’s disease (PD). Reducing the base of support from bipedal to unipedal stance increases center of pressure (CoP) parameters and intermuscular coherence in lower-leg muscles of healthy older adults. To further develop an understanding of postural control in an altered state of neurological impairment, we explored intermuscular coherence in lower-leg muscles and CoP displacement in older adults with PD. This study measured surface EMG from the medial (MG) and lateral (LG) gastrocnemii, soleus (SOL), and tibialis anterior (TA), and examined EMG amplitude and intermuscular coherence during bipedal and unipedal stance on a force plate with firm (no foam) and compliant (standing on foam) surface conditions in nine older adults with PD (70±5 years, 6 females) and 8 age-matched healthy older adults (5 females). Intermuscular coherence was analyzed between agonist-agonist and agonist-antagonist muscle pairs in the alpha (8-13 Hz) and beta (15-35 Hz) frequency bands. CoP parameters increased from bipedal to unipedal stance in both groups (p<0.01), but did not increase from the firm to compliant surface condition (p>0.05). During unipedal stance, CoP path length was shorter in older adults with PD (2027.9 ± 1074.1 mm) compared to healthy older adults (3128.5 ± 1198.7 mm) (p<0.01). Alpha and beta agonist-agonist and agonist-antagonist coherence increased by 28% from bipedal to unipedal stance (p<0.05), but did not differ between older adults with PD (0.09 ± 0.07) and healthy older adults (0.08 ± 0.05) (p>0.05). The older adults with PD also had greater normalized EMG amplitude of the LG (63.5 ± 31.7%) and TA (60.6 ± 38.4%) during the balance tasks (p<0.05) than their healthy counterparts. Older adults with PD had shorter path lengths during unipedal stance and required greater muscle activation than healthy older adults to perform the tasks, but intermuscular coherence did not differ between the groups. This may be attributable to their early disease stage and high motor function.